Prophylaxis of emesis induced by high emetogenic chemotherapy: a comparison between clinical practice and treatment guidelines. Issue 2 (12th March 2012) - Agostino, E.; Pugi, A.; Colombini, S.; Vaiani, M.; Cecchi, M.
Abstract : Background: According to European Society for Medical Oncology (ESMO) guidelines (2011), the preferred treatment for acute emesis induced by highly emetogenic chemotherapy (HEC) consists of the administration of a 5HT3 receptor antagonist (granisetron, ondansetron or palonosetron) and dexamethasone, plus aprepitant (known as triple therapy, TT). In the Anticancer Drugs Unit of Careggi Hospital (CH) of Florence, the ancillary treatment included in chemotherapy protocols is managed by using software shared with physicians. In this way the ancillary therapies can be modified at the time of prescription. Purpose: The aim of the study was to verify the correspondence between emesis treatment guidelines and the real clinical practice in our hospital wards. Materials and methods: Antiemetic medicines administered in CH wards in a two-month period (April-May 2011) were assessed using the treatment management software. Of particular interest were the days in which cisplatin was used at a dose higher than 50 mg/m 2 (alone or in association with other antineoplastic drugs), dacarbazine at all doses and combinations, and cyclophosphamide and anthracyclines included in breast cancer protocols. Results: In the reference period, 137 days' treatment with HEC were performed. Cisplatin administration was associated with TT in 42.4% of cases (dexamethasone 8-32 mg), and in the remaining 57.6% treatment with dexamethasone (16-20 mg) associated with a 5HT3-RA (mainly granisetron 3 mg) was preferred. Dacarbazine was administered as part of TT (palonosetron plus aprepitant) in 17.4%. In the majority of cases (82.6%) it was used only with palonosetron. Finally the TT regimen was given only in 1 out of 15 days' therapy during cyclophosphamide and anthracycline treatment. Conclusions: The availability of the chemotherapy management software allows us to have information about drug consumption. Our study shows that antiemetic prophylaxis for HEC is not always prescribed according to international guidelines.